Voices for Young Learners: Designing Podcast-Based English Materials through the ADDIE Model - Soviyah Soviyah; Nur Hidayanto P.S.P; Michelle R. Dee; Lorralie F. Canape; Bayu R.P. (Journal of Education and Teaching (JET), 2025)
This study addresses the limited and underexplored use of podcasts in Teaching English to Young Learners (TEYL) in Indonesia—a gap in the integration of digital audio media into early language learning. It develops and evaluates podcast-based English materials for fifth graders using the ADDIE model within a research and development framework. The process involved five stages: needs analysis, design, development, implementation, and evaluation. Participants included 40 students, English teachers, parents/guardians, and three experts (TEYL, media, and practitioner). Data were collected through questionnaires, interviews, classroom observations, expert validation, and student feedback, analyzed using descriptive quantitative and qualitative methods. Results show that the podcast materials were systematically designed to meet students’ necessities, lacks, and wants, and aligned with curriculum standards. Expert evaluations confirmed high quality (86.25% for content and 92.5% for media), while student responses (89.3%) reflected strong engagement, usability, and vocabulary support. This study contributes theoretically by addressing the empirical gap in TEYL podcast research in Indonesia, demonstrating the practical value of podcasts as flexible tools for young learners, and offering pedagogical and policy insights for integrating digital media into primary English instructions.